Melanotic Schwannoma of the Vagina: A Report of a Very Rare Tumor and Review of the Literature - Kofi Effah; Stefan Seidl; Edith Gorges; Patrick Kafui Akakpo (Case Reports in Obstetrics and Gynecology)
Melanotic schwannoma (MS) is a rare nerve sheath tumor with fewer than 200 cases reported. MS has uncertain malignant potential and comprises 1% of all nerve sheath tumors with a predilection for the spinal nerve roots. An even rarer location for this tumor is the vagina. Up to 55% of MSs that contain psammoma bodies are associated with the Carney complex, an autosomal dominant syndrome. Criteria for malignancy in MS are still not well established and long term follow-up of patients is recommended. A 26-year-old woman presented with a bleeding vaginal tumor which was diagnosed as MS following excision. The clinical, histopathological, and immunohistochemical features of this tumor are discussed.